2004
DOI: 10.1051/rnd:2004043
|View full text |Cite
|
Sign up to set email alerts
|

Hormones, IgG and lactose changes around parturition in plasma, and colostrum or saliva of multiparous sows

Abstract: -Blood, colostrum and saliva samples were serially taken from 6 multiparous sows from day 109 of gestation until day 3 postpartum. Plasma was assayed for oestradiol-17β (E2), progesterone (P4), prolactin (PRL), cortisol, immunoglobulin G (IgG) and lactose. Colostrum was assayed for E2, P4, IgG and lactose. Lactoserum, obtained after ultra centrifugation of colostrum, was assayed for PRL. Saliva was assayed for cortisol. Time-related variations in hormone, IgG and lactose concentrations measured in plasma were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 56 publications
8
36
1
1
Order By: Relevance
“…Hormonal concentrations in colostrum were also comparable with previously obtained results (Devillers et al, 2004a), with the exception that E2 concentrations were greater during farrowing in the present study. Hormonal status regulates the synthesis of colostrum components and the PCA analysis provides a good summary of the relationships between hormone concentrations and colostrum composition.…”
Section: Figuresupporting
confidence: 92%
See 2 more Smart Citations
“…Hormonal concentrations in colostrum were also comparable with previously obtained results (Devillers et al, 2004a), with the exception that E2 concentrations were greater during farrowing in the present study. Hormonal status regulates the synthesis of colostrum components and the PCA analysis provides a good summary of the relationships between hormone concentrations and colostrum composition.…”
Section: Figuresupporting
confidence: 92%
“…Although hormonal concentrations in colostrum and plasma are well correlated during parturition (Devillers et al, 2004a), the concentrations measured in colostrum reflect an average of plasma concentrations during an undetermined period and slight differences may therefore go unnoticed. A positive relationship between milk production and milk lactose concentrations was previously reported in sows (White et al, 1984), yet the inverse relationship found with the PLS analysis suggests that mechanisms regulating the synthesis of colostrum are different from those regulating milk synthesis.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…The assay sensitivity was 1.9 ng/ml. The plasma samples collected at T 24 and at weaning and the colostrum samples were analyzed for IgG concentration using a previously described ELISA method (Devillers et al, 2004a) with a sensitivity of 23 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…E100-104), according to an adaptation by I. Oswald (UR66 Pharmacologie-Toxicologie, INRA, Toulouse, France). The validated procedure was described by Devillers et al (2004a). Colostrum was diluted at 1/500 000 (t 0, t 3 and t 6 samples) or at 1/100 000 (t24 samples) and milk was diluted at 1/5000 (mid-lactation) and 1/2000 (late lactation).…”
Section: Biological Analysesmentioning
confidence: 99%